Sie sind auf Seite 1von 4

###

###
### ###
### +1 +7 a) - + a) + ( + 6) - ( - 12) = 6 + 12 = 18
###
###
### + ###
### - 1### -
b) + b) - ( - 2) - ( + 2) = 2-2= 0
###
###
### + - 3 ###
###### 1
c) - c) - ( + 5) + ( - 5) = -5 - 5 = -10
###
###### +1 +1 ###
### 3
d) + d) + ( - 14) + ( + 10) = -14 + 10 = -4
###
###
###
###### - ###
- ### -
e) + e) - ( - 6) + ( + 13) = 6 + 13 = 19
###
###
###
###### - ###
+ ### -
f) - f) - ( - 3) - ( + 9) = 3-9= -6
###
###### +1 +5 ###
### 1
g) - g) + ( + 15) - ( - 9) = 15 + 9 = 24
###
###### - 1 +2 ###
### 8
h) + h) - ( - 6) + ( - 1) = 6-1= 5
###
###
### + ###
### - 1### 1
i) + i) + ( + 8) + ( + 10) = 8 + 10 = 18
###
###
### - - 8 ###
###### 2
j) + j) - ( + 10) + ( + 1) = -10 + 1 = -9
###
###
### + - 0 ###
###### -
k) - k) + ( + 12) + ( + 14) = 12 + 14 = 26
###
###
### + - 2 ###
###### 1
l) - l) + ( - 10) - ( - 11) = -10 + 11 = 1
###
###
###
###### - ###
+ ### -
m) - m) + ( + 3) + ( - 12) = 3 - 12 = -9
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
######
a9 a)
Try again…
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
######
b5 b)
###
###
###
###
###
###
###
- ###
###
###
###
###
###
###
###
###
###
c- c)
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
######
d2 d)
###
###
###
###
###
###
###
- ###
###
###
###
###
###
###
###
###
###
e- e)
Try again…
###
###
###
###
###
###
###
- ###
###
###
###
###
###
###
###
###
###
f- f)
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
######
g5 g)
###
###
###
###
###
###
###
- ###
###
###
###
###
###
###
###
###
###
h- h)
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
######
i1 i)
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
######
j1 j)
Try again…
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
######
k5 k)
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
###
######
l1 l)
###
###
###
###
###
###
###
- ###
###
###
###
###
###
###
###
###
###
m- m)
+ ( - 7) - ( - 9) - ( + 3) - ( + 10) = - 7 + 9 - 3 - 10 =
- ( + 7) - ( + 11) - ( + 0) - ( - 14) = - 7 - 11 - 0 + 14 =
+ ( - 12) - ( - 6) - ( - 9) - ( - 13) = - 12 + 6 + 9 + 13 =
+ ( - 1) + ( - 1) + ( + 15) + ( - 13) = - 1 - 1 + 15 - 13 =
- ( - 12) - ( - 4) - ( + 2) + ( + 11) = 12 + 4 - 2 + 11 =
- ( - 3) - ( + 10) + ( - 8) - ( + 7) = 3 - 10 - 8 - 7 =
- ( - 6) + ( - 1) - ( - 14) + ( - 14) = 6 - 1 + 14 - 14 =
+ ( + 7) - ( - 3) + ( - 2) - ( - 9) = 7+3-2+9=
- ( + 15) - ( + 4) + ( - 7) - ( + 4) = - 15 - 4 - 7 - 4 =
- ( - 4) + ( - 13) - ( - 0) + ( + 8) = 4 - 13 + 0 + 8 =
- ( - 7) + ( + 15) + ( - 4) + ( - 4) = 7 + 15 - 4 - 4 =
+ ( + 6) + ( - 0) + ( - 11) + ( - 5) = 6 - 0 - 11 - 5 =
+ ( - 8) + ( - 10) + ( - 8) + ( + 3) = - 8 - 10 - 8 + 3 =
-11 0

-4 0
Try again…
16 0

0 1

25 0

-22 0
Try again…
5 0

17 0

-30 0

-1 0

14 0
Try again…

-10 0

-23 0